Which joints and why do rheumatologists scan in rheumatoid arthritis by ultrasonography? A real life experience - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2017)
Objective. Ultrasonography (US) has been demonstrated to improve assessment of synovitis and disease activity in rheumatoid arthritis (RA). However, the utility and feasibility of US in RA in clinical practice in real life is not known. We aimed to investigate: i) the indications for performing US in RA in daily practice; and ii) whether the number of scanned joints varies according to the purpose. Methods. Consecutive patients who had a US scan either for diagnosis or follow-up for RA from 5 centres were recruited. The sonographers were asked to mark the joints that had a US scan and grade their findings. Descriptive analysis was applied to find out the sites and the number of joints scanned and compared according to the indications of US. Results. Two hundred consecutive patients were recruited. The most common indication was assessing disease activity (48.5%) followed by diagnosis (45.5 %). Wrists (66%) and MCPs (63.5) were the most frequently scanned joints followed by knees (26%), PIPs (20%). The number of joints scanned by US was significantly higher when performed for diagnostic purposes as compared to assessing disease activity and guidance for injections (p=0.001). Conclusion. The current data highlight differences between the numbers of joints for which that the clinician feels necessary to perform US in real life. This observation may be a guide when providing recommendations regarding which joints need to be scanned according to the indication.
Keywords: rheumatoid arthritis; ultrasonography; disease activity; MUSCULOSKELETAL ULTRASOUND; INTEROBSERVER RELIABILITY; CLINICAL REMISSION; TASK-FORCE; RECOMMENDATIONS; SYNOVITIS; DISEASE; TARGET